TIPOLOGI KEPEMIMPINAN KYAI PESANTREN - Puadi, Hairul (Pascasarjana Universitas Al-Qolam Malang, 2024)
One of the most important and central elements in the system that applies in the world of Islamic boarding schools is the Kyai, even the legal owner of the Islamic boarding school. In this perspective, the Kyai needs to be observed as the main reference and referral for the students who become the central, authoritative and central figure of all policies and changes. Kyai is one of the elements in the definition of Islamic boarding school besides pondok (dormitory), mosque, students and teaching of classical Islamic books. Typology of leadership of Islamic boarding school caretakers: (1) Cultural Leadership. Leadership that maintains the culture of Islamic boarding schools which includes independence, empowerment, trust, synergy, and responsibility. (2) Strategic Leadership. Leadership based on three dimensions, namely time, scale of issues and scope of action. (3) Transformative Leadership. Leaders who have the capacity to work together, identity (personal platform), are able to communicate, can display many leadership styles, and can respond to trends and issues. (4) Responsive Leadership. Leadership that is part of the transformative leadership pattern that is responsive to needs. The miniature leadership style of the Kyai can be described as: (1) Autocratic type. (2) Militaristic type. (3) Paternalistic type. (4) Charismatic type. (5) Democratic type.